The Role of Islamic Religious Education as an Anti-Drug Activist Based on Islamic Development - Ahmad Saefulloh; Ferry Setiawan; Dafrizal Dafrizal; Hasnah Hasnah (Sekolah Tinggi Agama Islam Pengembangan Ilmu Al-Qur`an Sumatera Barat, 2023)
This article is motivated by the important role of Islamic religious education in collaboration with parties handling narcotics, alcohol, psychotropics, and addictive substances by involving students as anti-narcotics, alcohol, psychotropic and addictive substances activists in tackling the circulation of narcotics. The purpose of this article is to find out about higher education educators' programs with the government in anti-narcotics, alcohol, psychotropic and addictive substances activities. The research method used was descriptive qualitative by analyzing the results of interviews and documentation studies. The data collection technique is carried out using snowball sampling to obtain broad and specific data. The author concludes that the role of islamic religious education in higher education as anti-narcotics, alcohol, psychotropic substances and addictive substances based on islamic-based development cannot be separated from the role of the National Narcotics Agency, both provincial and city, through First Goes to Campus program; collaboration between the City National Narcotics Agency and the education unit. Second, the literacy program is a collaborative program between the National Narcotics Agency and universities, Islamic organizations as well as mass media, radio and other agencies. Third, through a program to recruit volunteers and activists; additional personal staff from the private sector, non-governmental organizations, academic circles who function as a liaison for the activities of the City National Narcotics Agency with agencies and the community and always actively provide information regarding developments in drug trafficking in the surrounding environment